2012
DOI: 10.4103/1735-3327.104875
|View full text |Cite
|
Sign up to set email alerts
|

Surface discoloration of composite resins: Effects of staining and bleaching

Abstract: Background:The purpose of this in vitro study was to evaluate surface discoloration of three microhybrid composite resins (Esthet•X HD, Clearfil AP-X, Gradia Direct) and five nanohybrid composite resins (Ceram•X, GC Kalore, G-aenial, Grandio, GrandioSO), after staining and bleaching procedures.Materials and Methods:The composite resins were polymerized with a curing light (Celalux II, Voco, Cuxhaven, Germany) into 160 silicon molds (6,4 mm in diameter and 2 mm in thickness) to obtain identical specimens. Twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
54
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 16 publications
10
54
1
2
Order By: Relevance
“…∆E values for CX and GA were low compared to other materials in the same investigation. In a previous study, the same authors reported that microhybrid and nanohybrid composites responded similarly when immersed in tea for 14 days [6]. A somewhat similar trend is reported in this investigation (illustrated clearly in Figure 2) with very little difference between microhybrids and nanohybrids expect CX, which is considered a nanoceramic with a novel and different resin matrix chemistry involving polysiloxane, polyurethane methacrylate, and ethoxylated bisphenol-A dimethacrylate (Bis-EMA).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…∆E values for CX and GA were low compared to other materials in the same investigation. In a previous study, the same authors reported that microhybrid and nanohybrid composites responded similarly when immersed in tea for 14 days [6]. A somewhat similar trend is reported in this investigation (illustrated clearly in Figure 2) with very little difference between microhybrids and nanohybrids expect CX, which is considered a nanoceramic with a novel and different resin matrix chemistry involving polysiloxane, polyurethane methacrylate, and ethoxylated bisphenol-A dimethacrylate (Bis-EMA).…”
Section: Discussionsupporting
confidence: 87%
“…In order for the esthetic restorative materials to be functional, they need to maintain color and shade in order to blend with the neighboring tooth structure. This property is important both in the short term after curing as well as in the long term during function [4,6,7]. Clinically unacceptable color change of resin composites is the primary reason for restoration replacement especially in the anterior region of the oral cavity [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Embora a cor de uma restauração possa ser estável ao longo do tempo, mudanças podem ocorrer por: pigmentação da superfície, pigmentação marginal, microinfiltração, desgaste da superfície e deterioração interna do material 20 . A hipótese deste estudo foi aceita, pois os agentes clareadores não alteraram a dureza, mas alteraram a cor dos materiais restauradores testados.…”
Section: Discussionunclassified
“…Moreover, the structure of the composite resin and the characteristics of its particles have a direct influence on the susceptibility to extrinsic staining. (2 ) Bleaching is an effective and conservative esthetic treatment for removing intrinsic and extrinsic stains from teeth. The bleaching agent usually contains peroxide (in the form of carbamide and hydrogen peroxide) in gel or liquid form.…”
Section: Methodsmentioning
confidence: 99%
“…The L* coordinates are located along a vertical axis that ranges from 0 (completely black) to 100 (completely white); (9)(10)(11)(12)(13) a* uses positive values (+a*) to denote red colors and negative values (-a*) to denote green colors; and b* depicts yellow color with positive values (+b*) and blue color using negative values (-b*). (2) Before each measurement session, the instrument was calibrated according to the manufacturer's recommendations. Color measurement was conducted on the top surface of each specimen against a white background.…”
Section: Color Assessmentmentioning
confidence: 99%